Fungal degradation of lignin-based rigid polyurethane foams - Sepúlveda, Manuel Martinho Vilas Boas (2011)
The environmental impacts arising from the use of polymeric materials is a serious problem since they can present long periods of degradation and hence being accumulated in the environment. Polyurethanes (PU) are considered as one of the most versatile polymeric materials offering a wide range of products with applications in diverse sectors. Rigid polyurethane (RPU) foams, due to its excellent insulation and mechanical properties, are widely used in construction, automotive, freeze industry and nautical applications. In this context, the use of green polyols with value-added properties, such as biodegradability, will contribute to reduce environmental impacts. In this work the ability of Aspergillus niger to degrade lignin-based RPU foams in comparison with a control (RPU foam based on a commercial polyol), was tested according to various procedures.